2020
DOI: 10.1021/acs.langmuir.0c00996
|View full text |Cite
|
Sign up to set email alerts
|

Surface Preconditioning Influences the Antifouling Capabilities of Zwitterionic and Nonionic Polymer Brushes

Abstract: Polymer brushes not only represent emerging surface platforms for numerous bioanalytical and biological applications but also create advanced surface-tethered systems to mimic real-life biological processes. In particular, zwitterionic and nonionic polymer brushes have been intensively studied because of their extraordinary resistance to nonspecific adsorption of biomolecules (antifouling characteristics) as well as the ability to be functionalized with bioactive molecules. However, the relation between antifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…Using the available methods (for more details, see also the Supplementary Materials), a direct determination was found to be quite challenging. For example, while the level of immobilized RGD peptides on OEG SAM was quantified by the SPR method, it was not possible to determine the RGD-peptide surface concentration on the pCB-based coatings due to a very high pCB-based zwitterionic surface hydrophilicity [33,39,53] combined with a relatively small molecular weight of the RGD peptide ( Figure S2 in the Supplementary Materials). Therefore, we were not able to directly compare the level of functionalization of pCBAA, pCBMAA-based coatings, and OEG-based coatings.…”
Section: Discussionmentioning
confidence: 99%
“…Using the available methods (for more details, see also the Supplementary Materials), a direct determination was found to be quite challenging. For example, while the level of immobilized RGD peptides on OEG SAM was quantified by the SPR method, it was not possible to determine the RGD-peptide surface concentration on the pCB-based coatings due to a very high pCB-based zwitterionic surface hydrophilicity [33,39,53] combined with a relatively small molecular weight of the RGD peptide ( Figure S2 in the Supplementary Materials). Therefore, we were not able to directly compare the level of functionalization of pCBAA, pCBMAA-based coatings, and OEG-based coatings.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the choice of the characterization technique influences the portion of fouling properties that are observed, and thus potentially leads to different results obtained for the same sample. 191,192 This section provides a brief overview of the techniques and experimental conditions most frequently used for fouling measurements with an emphasis on their major limitations.…”
Section: Methods For Assessment Of Foulingmentioning
confidence: 99%
“…86,197 Moreover, the SPR technique may be prone to the interference of the refractive index changes caused by the bound mass with refractive index changes caused by swelling of highly hydratable structures. 192…”
Section: Impact Of Functionalization On Foulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many techniques use sensors or surfaces that are coated with low-fouling materials; grafting efficiency will therefore further introduce variability. Additionally, it has recently been shown that minor deviations during sample preparation for characterization techniques can also impact fouling levels (Visova et al, 2020). To overcome these differences in sample preparation, as well as reduce variability between samples, several techniques for characterizing low-fouling coatings have been extended to high-throughput screening (HTS) (Hook et al, 2010(Hook et al, , 2012Magennis et al, 2016).…”
Section: Methods For Quantifying Bulk Protein Fouling On Planar Surfacesmentioning
confidence: 99%